Study of biological and management of fisheries of squid (Loligo sp.) that was land at PPP Tasik Agung Rembang - Pertiwi, Rahmasari Gita; Ghofar, Abdul; Fitri, Aristi Dian Purnama (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Squid is a family of Loliginidae which consists of 8 genera, of which 3 genera of which have important economic value, namely Loligo, Sepioteuthis and Uroteuthis. One of the catches in Rembang waters which is quite high is the squid fishery which landed at PPP Tasik Agung. The most common types of squid landed at PPP Tasik Agung are Loligo chinensis, Loligo duvaucelli, and Loligo edulis. The purpose of this research is to know the biological condition of squid, the condition of capture fisheries, and to know the management that can be done. The study was conducted from June to July 2022. Random sampling method is the method used in sampling. Analysis of the data used is the relationship between length and weight, sex ratio, gonad maturity level, size at first caught and mature (Lc and Lm), and EAFM domain of fish resources. The results showed that the capture of squid is still not well controlled. The results of the t-test measuring the length-weight relationship of the three species that have been found indicate that the growth is allometric negative. As many as 49.6% of the three types of squid that have been caught are indicated to be immature gonads because they have been dominated by TKG I and II. The ratio of male and female sex of all samples is 1: 0.54. The overall composite indicator assessment result on the fish resource domain indicator is 0.48 (48%). One of the strategies in the management of squid fisheries that can be done is to make regulations for limiting fishing efforts and the minimum size of fish that can be caught.